Calcareous Nannofossils Biostratigraphy of Tanjero Formation at Azmer anticline Northern Iraq - Al-Sulevani, Rahme Fares; Al-Badrani, Omar Ahmed (Iraqi Journal of Science, 2021)
Seventy three species of calcareous nannofossils are recorded from the studied section of Tanjero Formation at Azmer anticline, Sulimaniya, Northern Iraq. The studied section reveals four biozones arranged in an ascending order from oldest to youngest as follows; Tranolithus phacelosus Interval Biozone (CC23) Part, Rienhardtites lives Interval Biozone (CC24), Arkhangelskilla cymbiformis Interval Biozone (CC25), and Nephrolithus frequens Rang Biozone (CC26) Part. These biozones are correlated with other calcareous nannofossil biozones of both local and regional sections, leading to conclude a possible age of Late Campanian- Maastrichtian.